Network functions virtualization (NFV) with a touch of SDN - Chayapathi, Rajendra; Hassan, Syed Farrukh;Shah, Paresh (Boston, Massachusetts : Addision-Wesley Publishing Company, 2017)
Network Functions Virtualization (NFV) will drive dramatic cost reductions while also accelerating service delivery. Using NFV with SDN, network owners can provision new functions rapidly on demand, improve scalability, and leverage microservices. Benefits like these will make NFV indispensable for service providers, mobile operators, telcos, and enterprises alike. Network Functions Virtualization (NFV) with a Touch of SDN is the first practical introduction to NFV$1 (Bs fundamental concepts, techniques, and use cases. Written for wide audiences of network engineers, architects, planners, and operators, it assumes no previous knowledge of NFV architecture, deployment, or management. The authors first explain how virtualization, VMs, containers, and related technologies establish the foundation for the NFV transformation. Next, they show how these concepts and technologies can be applied to virtualize network functions in the cloud, data centers, routing, security, and the mobile packet core. You$1 (Bll discover new tools and techniques for managing and orchestrating virtualized network devices, and gain new clarity on how SDN and NFV interact and interrelate. By the time you$1 (Bre done, you$1 (Bll be ready to assess vendor claims, evaluate architectures, and plan NFV$1 (Bs role in your own networks. s
Keywords: COMPUTER NETWORK ARCHITECTURES